MELAUDIS: The First Acoustic ITS Dataset in Urban Environment - Hossein Parineh (19743985) (2024)
The MELAUDIS dataset consists of two sections: 1) MELAUDIS_BG: This section contains background noise recorded at various locations in Melbourne, capturing a broad range of environmental sounds such as car horns, people talking, walking, laughing, music from cars and stores, wind, rain, dogs barking, birds chirping, and more. 2) MELAUDIS_Vehicles: This section is organized into 20 folders representing different data collection points. It includes data on vehicles in various traffic conditions, such as those stuck in traffic or moving in free-flow, categorized into six vehicle types. Each sample is also labeled with the lane number in which the vehicle is moving.